La génesis del proceso de divinización de Jesús el Galileo. Ensayo de status quaestionis - Bermejo Rubio, Fernando (ARYS. Antigüedad: Religiones y Sociedades, 2015)
As far as Judaism is deemed to be a strict Monotheism, any deifying process occurring within this religion appears to be a remarkable fact. As is well-known, however, the Galilean preacher Jesus of Nazareth came to be revered in the most exalted terms –comprising divinization– in some trends of the initially Jewish movement that later became what we call «Christianity». This article provides an assessment of the history of research carried out in the last century (from Wilhelm Bousset’s work to the very present) by identifying and examining the main explanations for the emergence of Jesus’ divinization within Jewish and Greco-Roman settings.
Keywords: deification; Jesus; Judaism; Hellenism; Wilhelm Bousset